Influence of polymer architectures on diffusion in unentangled polymer melts. Issue 34 (2nd August 2017) - Chremos, Alexandros; Jeong, Cheol; Douglas, Jack F.
Abstract : Molecular dynamics simulations of polymer melts composed of polymers of different branching complexity suggests that the average polymer shape and hydrodynamic radius are important for the understanding of the polymer diffusion, as in polymer solutions. Abstract : Recent simulations have indicated that the thermodynamic properties and the glassy dynamics of polymer melts are strongly influenced by the average molecular shape, as quantified by the radius of gyration tensor of the polymer molecules, and that the average molecular shape can be tuned by varying the molecular topology ( e.g., ring, star, linear chain, etc. ). In the present work, we investigate if the molecular shape is similarly a predominant factor in understanding the polymer center of mass diffusion D in the melt, as already established for polymer solutions. We find that all our D data for unentangled polymer melts having a range of topologies can be reasonably described as a power law of the polymer hydrodynamic radius, R h . In particular, this scaling is similar to the scaling of D for a tracer sphere having a radius on the order of the chain radius of gyration, R g . We conclude that the chain topology influences the molecular dynamics in as much as the polymer topology influences the average molecular shape. Experimental evidence seems to suggest that this situation is also true for entangled polymer melts.